Tweeting the Drug War: Empowerment, Intimidation, and Regulation in Social Media - Kiciman, Emre; boyd, danah; Counts, Scott; Monroy-Hernández, Andrés (Human Computer Interaction International Conference, 2012)
In this paper, we describe how people living in armedconflict environments use social media as a participatory news platform. We investigate this by analyzing the microblogging practices of people living amid the Mexican Drug War. This paper provides a descriptive analysis of the phenomenon by mixing quantitative observations, content analysis, interviews, and case studies. We characterize the volume, temporal attributes, and information sharing methods. We focus on how citizens use social media to alert and disseminate information about acute violent events, and to interact with other people in their localities. We describe how social media might start to function in lieu of damaged state and news media apparatuses, in particular, through the emergence of communities that congregate around hashtags and the citizens that curate them. Finally, we explore the tensions among citizens, media actors, and the government in light of generalized violence and distrust in institutions and citizens. We end by outlining the implications for system design and governmental intervention.